Biblioshiny-R Application to Map Hajj Management Research - Puspita, Amelia Tri; Taufiq, Muhammad (SMART Insight, 2023)
Hajj is an act of worship that must be performed by all Muslims who have the ability both outwardly, inwardly, and also financially. The obligation to perform the Hajj is only done once in a lifetime. There is an external assessment that the management of the implementation of the Hajj pilgrimage has not been effective in terms of institutional aspects, financial management, and improvement of facilities and infrastructure in providing services to pilgrims. Therefore, there is a need for management of the Hajj pilgrimage as an effort to improve the system of organizing Hajj that is better, professional, and accountable. This study aims to determine the development map and trend of Hajj Management published by reputable journals. The data analyzed were more than 243 Google Scholar indexed research publications. The export data was then processed and analyzed using the R Biblioshiny application program to find out the bibliometric map of Hajj Management development. The results showed that We have identified two research networks in Hajj Management literature using co-occuerence network. These research networks are